Designing and Articulating the Model of Sustainable Nation-Building - Ghazaleh Taheri Attar (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2014)
Throughout history, many nations are formed; nations with various specificationsthat relied on their favorable traits guided the next generation and formed the nextcommunities. Sometimes they were in the form of nations but suffer from the lack theorganization and without any collective wisdom and due to mismanagement theywere doomed to extinction. So, the question is “what factors and requirements areneeded to shape a virtue nation and guarantee its survival?”In this paper, we aim to answer the above mentioned question. In this way we triedto analyze the articles and literature in nation-building and good governanceaccording to the grounded theory and content analysis to find out the factors andstrategies for maintaining and recognizing nation’s existence. Thus a modelconsists of three components was developed and designed. In order to evaluate,regulate and modify the designed pattern, by using Delphi method and alsoreferring to some elites in the field of research modeling, the model was presentedto 17 elites in two-round Delphi. In the second round of Delphi, the model wasapproved by elites so sustainable nation-building model was redesigned as a giftof nation-building in the light of good governance. This model consists of 3components: a) obligations of initiating nation- building (general and specificnational identity), b) strategies for continuing the processes for nation-building(social justice, effective government, citizenship, political socialization) and c)consequences of continuing existence of the nation and nation-building process(national integrity, public trust, permanent peace, balanced and sustainabledevelopment, national and international legitimacy).